(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
An online auction is a business strategy in which products are sold by placing bids based ontheir current market value. They have a starting price and a deadline. The auction has a number ofpotential purchasers, and the winner is the one who bids the highest price within the allotted time frame.Users who wish to purchase products online must supply their personal information, including theiremail address, phone number, and a scan of their Aadhaar card. It is now time to consider thesignificance of the role played by security. A URL with a set expiration time will be used to verify theemail address. An OTP is used to verify the phone number as well. To be able to bid, a user must beauthenticated. This stops a variety of online auction frauds from acquiring the trust of the customers.Secure Online Auction System is the gist of it. We can join in a bidding war for goods and services viaan online auction. The use of online software that regulates the processes involved simplifies theauction process.